Soil use and occupation and morphometric characterization of microbasin in the central south paranaense region - Oliveira, Darlin Henrique Ramos de (2018)
Disorganized exploitation of natural resources, inadequate use of land, associated with abusive use of fertilizers, correctives and agrochemicals has been causing several environmental issues, especially in areas of springs and meadows, harming the quality and quantity of water resources. Studies at the microbasin level can provide important information to the correct management and adequacy of the problems encountered. The aim of the present study was to study soil use and occupation, as well as to define the morphometric characteristics of the river Guarani basin, located in the rural area of Quedas do Iguaçu, Paraná, Brazil. In order to do so, four different maps were elaborated:  the drainage network map, the permanent preservation area (APP) map, soil use and occupation map, and the slope of the microbasin map. In addition, the morphometric analysis of the microbasin were performed, providing substantial data for further analysis. It should be noted that there are some irregularities in the micro-basin under study that could be solved with proper management in order to preserve water quality and mitigate erosive processes.